The National Programme for Improvement of Access and Quality of Basic Health Care and the work process organization. - Estela Auxiliadora Almeida LOPES; Magda Duarte dos Anjos SCHERER; Ana Maria COSTA (Universidade de Brasília, 2015)
This qualitative study analises the National Programme for Improvement of Access and Quality of the Basic Health Care focusing on the reorganization of work processes: self-evaluation, continuous education, institutional support and monitoring. Based on document analysis, direct observations and interviews with workers in the Federal District. The results point to lack of training of team members for the adherence to the programme; parcial/distorted view about its proposal; weakenesses in the monitoring; incipient self-evaluations processes; lack of institutional support; inadequate permanent education; unsatisfactory working conditions; and deficits in the support diagnosys network. It should be considered that changes in work processes require time to be implemented and that improvement in the quality of services goes beyound prescriptions and fullfilment of standards and norms.